Diseño de una metodología técnica operativa para la importación directa de equipos de automatización industrial para dispensadores desde Estados Unidos hacia Ecuador aplicado en la empresa Serpra Cía. Ltda, y en las pymes - Castillo Santillán, Andrea Jaqueline (2015)
The research aims to create a methodological guide that will improve processes for foreign trade company Serpra Cia Ltd., Chapter 1, the problem Serpra research focused on the processes involved in generating occurs inefficiency in foreign trade. In Chapter 2, the research is focused on the Company Serpra Cia. Ltd., located via a Conocoto Miravalle, who makes imports of industrial automation equipment for the manufacture of dispensers, the same as in the search for determining the appropriate process to improve their foreign trade department, for which the company must comply with all the proposed schemes in the investigation and that the proposed transaction is successful. In Chapter 3, the research methodology was conducted based on information provided by Serpra Cia. Ltd, and the National Customs Service of Ecuador SENAE addition to field research was conducted with foreign trade operators and Pymes to obtain primary information. In Chapter 4, after completing the investigation results determined that lack of knowledge in companies on foreign trade and therefore proposes a methodology to what they should do the same to avoid enormous expenses and lost time guide. In Chapter 5, the proposal will help guide for Pymes to develop the ability to perform foreign trade operations in the new portal Ecuapass custom, compliance with the law, regulations and resolutions established in our country, so that to save costs, improve organizational structure and route the appropriate processes to reduce times of imported inputs for which they are eligible importing Pymes and companies engaged in foreign trade operations.